The development of coumarin Schiff base system applied as highly selective fluorescent/colorimetric probes for Cu2+ and tumor biomarker glutathione detection. (April 2020) - Wang, Zhi-Gang; Ding, Xiao-Jing; Huang, Yu-Ying; Yan, Xiao-Jing; Ding, Bin; Li, Qing-Zhong; Xie, Cheng-Zhi; Xu, Jing-Yuan
Abstract: Overexpression of tumor biomarker glutathione (GSH) has been documented in numerous types of cancers, therefor GSH-activated light-up chemosensors for tumor identification require great attention. A new colorimetric/fluorescent probe (7-(diethylamino)-2-oxo-2H-chromen-3-yl)methylene)-4-(dimethylamino) benzohydrazide (HL) was prepared, which could be applied in discriminating Cu 2+ and further recognizing GSH based on its Cu complex. Firstly, the probe HL toward Cu 2+ exhibited selective fluorescence quenching and obvious color change from yellow to orange-red under visible light. Further, when GSH was introduced to the Cu 2+ -2HL system, the fluorescence recovered rapidly due to the high affinity of GSH to Cu 2+, meanwhile the color reverted back to former yellow. Based on fluorescence titration, the detection limits were calculated as 2.40 × 10 −8  M and 1.29 × 10 −7  M for Cu 2+ and GSH, respectively. The combination mode of HL with Cu 2+ was investigated in detail by Job plots, ESI-MS, FT-IR, and DFT studies. Probes HL and Cu 2+ -2HL showed relatively less toxicity and were employed for biological imaging in cells and zebrafish. Remarkably, the detection for endogenous GSH by this developed sensor platform implied great potential application prospect in cancer diagnosis. Graphical abstract: A highly selective fluorescent/colorimetric probe system for detecting Cu 2+ and tumor biomarker glutathione. Image 1 Highlights: New chemosensor for colorimetric and fluorescent detection of Cu 2+ and GSH. The probe displays high selectivity, excellent sensitivity and short response time. Fast recognition of Cu 2+ and GSH can be achieved by naked eye. Detecting endogenous and exogenous glutathione in living cells and zebrafish. Cancer identification was achieved by endogenous GSH sensing.